Mazmur sebagai Doa dan Pujian: Tafsir Teologis terhadap Dinamika Emosi dalam Kitab Mazmur 146-150 - Puling, Isak Petrus; BT, Abraham; Bambangan, Malik (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The Book of Psalms is an important part of the Old Testament worship and theology tradition, reflecting the dynamics of human emotions in their relationship with God. Psalms 146-150 specifically highlight aspects of prayer and praise as expressions of joyful and hopeful faith. This study aims to interpret theologically how these five psalms describe the emotional response of believers to the work and character of God. With an exegetical and biblical theological approach, this study finds that Psalms 146-150 form a climax in the structure of the Book of Psalms, emphasizing the supremacy of praise as the primary form of worship. In addition, this study highlights how the emotional aspects of these psalms function not only as a reflection of individual faith experiences but also as a collective appeal for the community of believers. Thus, Psalms 146-150 emphasize that prayer and praise are the primary means of expressing the relationship between humans and God, while inspiring a spiritual life centered on worship.